Being a good employee: Contribution of internal locus of control to work discipline - Emil Salim; Nefi Darmayanti; Mulia Siregar; Astri Delia Razi (INSPIRA: Indonesian Journal of Psychological Research, 2020)
Discipline is a condition of employee self-control and orderly behavior that indicates the true level of teamwork within an organization. One important but often difficult aspect of internal employee relations is the application of disciplinary action. This study aims to look at the relationship between the locus of internal control and the discipline of work. The subjects in this study were personnel of the Mobile Brigadier Unit in the North Sumatra Regional Police with a total of 80 personnel. The data analysis method used in this study was Pearson's correlation and obtained a very significant positive relationship between the locus of internal control and the work discipline, where r = 0.4714 and p < 0.01. This means that the higher the locus of internal control, the higher the work discipline. On the contrary the less locus of internal control, the lower the discipline of its work. The internal locus of control contributes to the work discipline of 0.510. This means 51% of internal locus control affects personnel work discipline. From this percentage, it can be stated that there is still 49% influence of other factors on the work discipline of Mobile Brigadier personnel, among them are leadership style factors, and work environment.